Optimizing endoscopic detection of early gastric cancer: stratification and preventive strategies for Peri-ESD diagnostic oversights - Zhang, Lei; An, Nana; Zheng, Xiuli; Ma, Wenqian; Lu, Juntao; Er, Limian (Frontiers in Oncology, 2026)
BackgroundPeri-endoscopic submucosal dissection missed early gastric cancers (peri-ESD MEGCs), defined as ESD-indicated lesions overlooked during pre-ESD diagnostic workup or post-ESD surveillance, may arise from deficiencies at any procedural phase (preparation, observation, diagnosis, or sampling). To address this, we developed a temporal-procedural bidirectional assessment protocol specifically targeting peri-ESD MEGCs, aiming to optimize endoscopic quality and prevent diagnostic omissions.MethodsIn this retrospective cohort study, 1,011 EGC lesions treated with endoscopic submucosal dissection (ESD) between 2017 and 2024 were analyzed. The primary analysis defined the MEGC time window as 24 months. Peri-ESD MEGCs were stratified into two temporal phases, pre-ESD examination vs. post-ESD surveillance, and four etiological categories, inadequate preparation, inadequate observation, diagnosis error, and sampling error, for each endoscopic cause of MEGC. To assess the robustness of our findings, a sensitivity analysis was performed by redefining the MEGC time window as 12 months.ResultsAmong 94 peri-ESD MEGCs, pre-ESD MEGCs (n=52) predominantly demonstrated inadequate observation (51.9%), which was associated with greater curvature location (OR: 5.45; 95% CI: 1.76–16.91), nonuse of near-focus narrow-band imaging (NF-NBI, OR: 16.78; 95% CI: 5.50–51.26), and severe intestinal metaplasia (OR: 3.84; 95% CI: 1.09–13.52). Post-ESD MEGCs (n=42) predominantly demonstrated a diagnosis error (52.4%), correlated with trainees (OR: 3.53; 95% CI: 1.06–11.68), small lesions (<15 mm, OR: 3.83; 95% CI: 1.10–13.36), nonuse of NF-NBI (OR: 17.44; 95% CI: 4.81–63.17), and severe atrophic gastritis (OR: 7.78; 95% CI: 1.91–31.20). The sensitivity analysis using a 12-month MEGC time window yielded results consistent with the primary analysis, demonstrating the robustness of the identified risk factors for peri-ESD missed lesions.ConclusionsOptimizing peri-ESD gastroscopic observation (via NF-NBI) and post-ESD diagnostic accuracy (through operator training) could significantly reduce peri-ESD MEGCs, particularly those reflecting characteristics of ESD-eligible lesions.